A Feminist Critique of the Practice of Polygamy in the Context of Islamic Law and Human Rights - Suud Sarim Karimullah (Indonesian Journal of Law and Islamic Law (IJLIL), 2024)
This study aims to identify the impact of polygamy practices on women's welfare, consider the gender justice issues that arise, and evaluate its relevance in the context of an Indonesian society that increasingly recognizes and strives for gender equality. This study uses a library research method with a holistic literature analysis to explore the topic comprehensively with an interdisciplinary approach. The results of the study show that feminist criticism highlights that polygamy reinforces patriarchal structures that place women in a position of subordination and dependence, as well as creating competition between wives for attention and resources from husbands who often do not share their time and affection fairly. Although positive law in Indonesia requires the permission of the first wife and proof of the husband's financial capability and fairness in polygamy, its implementation is often weak and fails to protect women's rights. Feminist perspectives emphasize the need for strict and human rights-oriented legal reforms, with rigorous monitoring mechanisms and empowerment of women through education of their rights, as well as changes in social and cultural views on polygamy to create an inclusive and fair environment for all individuals regardless of gender.